2007
DOI: 10.1002/prot.21446
|View full text |Cite
|
Sign up to set email alerts
|

Definition of an electrostatic relay switch critical for the cAMP‐dependent activation of protein kinase A as revealed by the D170A mutant of RIα

Abstract: The Regulatory (R) subunit of Protein Kinase A (PKA) inhibits its kinase activity by shielding the Catalytic (C) subunit from physiological substrates. This inhibition is reversed in response to extra-cellular signals that increase cAMP levels in the cytoplasm. Upon cAMP binding to R, C is allosterically released from R, activating a spectrum of downstream signaling cascades. Crystallographic data indicated that a series of distinct conformational changes within CBD-A must occur to relay the cAMP signal from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
(71 reference statements)
2
32
0
Order By: Relevance
“…It is important that the results confirm the importance of the Arg 209 /Asp 170 relay in propagating the effects of cAMP binding to the R-C interface. This is one region that showed decreased exchange upon (R p )-cAMPS binding and strongly suggests that the basis for the inability of (R p )-cAMPS to facilitate dissociation of the C-subunit is the uncoupling of the charge relay linking Arg 209 and Asp 170 and is consistent with previous mutagenesis data (26,29). In the C-subunit, changes in amide exchange occurred almost globally with single deuteron increases in fragments associated with the ␣A-␤1 loop, ␣F, ␣G, ␣G-␣H loop, ␣H-␣I loop, and the C-terminal tail.…”
Section: Camp-and (R P )-Camps-induced Conformational Changessupporting
confidence: 88%
See 1 more Smart Citation
“…It is important that the results confirm the importance of the Arg 209 /Asp 170 relay in propagating the effects of cAMP binding to the R-C interface. This is one region that showed decreased exchange upon (R p )-cAMPS binding and strongly suggests that the basis for the inability of (R p )-cAMPS to facilitate dissociation of the C-subunit is the uncoupling of the charge relay linking Arg 209 and Asp 170 and is consistent with previous mutagenesis data (26,29). In the C-subunit, changes in amide exchange occurred almost globally with single deuteron increases in fragments associated with the ␣A-␤1 loop, ␣F, ␣G, ␣G-␣H loop, ␣H-␣I loop, and the C-terminal tail.…”
Section: Camp-and (R P )-Camps-induced Conformational Changessupporting
confidence: 88%
“…Substitution of Lys for Arg at residue 209 blocks binding to the CNB-A site (26) and transforms (R p )-cAMPS into an agonist (27) Functionally, the binding of cAMP to the PBC can be considered as a phosphorylation event that acts as an electrostatic switch. Arguably, the most important moiety of cAMP involved in the activation process is its phosphate oxygen in the equatorial position (R p ) anchored by a critical, conserved Arg 209 (29). As discussed above, cAMP binding activates this electrostatic switch.…”
Section: Camp-and (R P )-Camps-induced Conformational Changesmentioning
confidence: 99%
“…5) , and Ile 206 in the PBC, Asp 172 (which interacts with the conserved Arg in the PBC), and the ␣C:A and ␣C':A helices are all sensitive to cAMP binding in the A site (14, 39 -41). Previous NMR studies on R truncated at position 246 also revealed communication between A site binding and the ␣C:A helix (11,12,30,42). However, the cumulative and sequential structural effect on the interdomain helices affected by binding of cAMP to both sites, as well as the communication of cAMP binding in the A site to the B domain, is observed here for the first time.…”
Section: Conformational Flexibility Of Apori␣ a Crucial Feature Forsupporting
confidence: 58%
“…First, the R 2 C 2 holoenzyme contains four binding sites for cAMP that are capable of communicating between each other, creating a cooperative effect of cAMP binding (9). Second, each CBD undergoes major structural changes during activation (10), and two of them (both CBD-As) have extended interfaces with the C-subunits that can interfere with the conformational changes (11,12). Thus, the unleashing of the C-subunits in the R 2 C 2 complex must also be a factor in the activation process.…”
mentioning
confidence: 99%
“…Thus, the unleashing of the C-subunits in the R 2 C 2 complex must also be a factor in the activation process. Because of the complexity of the system, it has been difficult to expand the NMR and crystal structure studies beyond a single CBD or an R-C heterodimer to the whole R 2 C 2 complex (12,13).…”
mentioning
confidence: 99%